Embolic stroke after carotid artery ligation during carotid body tumor resection. (February 2013) - Kim, Hyangkyoung; Cho, Yong-Pil; Moon, Ki-Myung; Kwon, Tae-Won
This report describes a case of a delayed cerebral embolic infarction, after internal carotid artery (ICA) ligation secondary to carotid body tumor resection. We describe a 34-year-old woman who underwent left ICA ligation during a large carotid body tumor surgery. Immediately after surgery, the patient was neurologically asymptomatic; however, she subsequently developed a cerebral embolic infarction nine hours postoperatively. After beginning antiplatelet therapy, all symptoms ultimately resolved, although over a gradual course. Since the ligation of the ICA can cause thromboembolic infarctions of the cerebrum, we contend that antiplatelet agents be administered to prevent and/or treat embolic strokes.